2002
DOI: 10.1017/s0030605302000492
|View full text |Cite
|
Sign up to set email alerts
|

Heavy poaching in prime habitat: the conservation status of the West Indian manatee in Nicaragua

Abstract: This study provides an overview of the conservation status of the West Indian manatee Trichechus manatus in Nicaragua, including data on habitat availability, manatee distribution and relative abundance, and current threats. The data is based on surveys from boats and extensive interviews with local people. Nicaragua harbors one of the largest areas of habitat suitable for manatees in Central America. The species has an almost continuous distribution along the country's eastern, Caribbean coast and inland in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 0 publications
1
21
0
3
Order By: Relevance
“…Furthemore Colmenero and Hoz (1986), Jiménez (2002), Horikoshi-Beckett and Schulte (2006) reported more crepuscular and nocturnal activity in manatees, probably in response to less human activity overnight. It is likely since in this study the manatees were exposed to a public environment enclosure, the result is that there is more diurnal activity as opposed to night activity.…”
Section: Discussionmentioning
confidence: 95%
“…Furthemore Colmenero and Hoz (1986), Jiménez (2002), Horikoshi-Beckett and Schulte (2006) reported more crepuscular and nocturnal activity in manatees, probably in response to less human activity overnight. It is likely since in this study the manatees were exposed to a public environment enclosure, the result is that there is more diurnal activity as opposed to night activity.…”
Section: Discussionmentioning
confidence: 95%
“…The resting behavior also increased during the afternoon. Manatees have been described as arrhythmic (Hartman 1979;Reynolds, 1981), although in areas with marked human activity, they seem to be more active at dawn, dusk and during nighttime (Colmenero and Hoz 1986;Jiménez 1999;Jiménez 2002;Horikoshi-Becket and Shulte 2006). While studying animals in captivity, Holguin et al (2015) found a circadian cycle of the resting behavior, with manatees being more active during the day, which is consistent with other studies of manatees in captivity (Hénaut et al 2010, Kikuchi et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…During low tides and the dry season in Venezuela and Costa Rica, they often take refuge in holes or channels in the rivers that range from 6 to 12 m in depth (O'Shea et al, 1988;Smethurst & Nietschmann, 1999). Anecdotal observations suggest that manatees in Nicaragua rest in quiet, sheltered, deep water during most of the day, leaving to feed only during the night, early morning, and late afternoon (Jiménez, 2002). In Belize, resting behavior has been correlated with the presence of a "resting hole" (CSS & K. LaCommare, unpub.…”
Section: Introductionmentioning
confidence: 97%